N'-(1-Allyl-2-oxoindolin-3-ylidene)benzohydrazide - Alsubari, A.; Moussaif, A.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C(18)H(15)N(3)O(2), the dihedral angle between the ring systems is 15.1 (1)degrees. The amino H atom is hydrogen bonded to the exocyclic O atom of the five-membered ring, forming an S(6) motif